Decreased Trabecular Bone Score in Patients With Active Endogenous Cushing’s Syndrome - Stachowska, Barbara; Halupczok-Żyła, Jowita; Kuliczkowska-Płaksej, Justyna; Syrycka, Joanna; Bolanowski, Marek (Frontiers in Endocrinology, 2021)
Introduction: The impairment in bone microarchitecture and reduced bone quality are relevant mechanisms underlying the increased fracture risk in Cushing’s syndrome (CS). The trabecular bone score (TBS) is a relatively novel textural index of bone microarchitecture. Purpose: The objective of study was to compare TBS, bone mineral density (BMD) and fracture risk in patients with endogenous CS to controls. We have investigated association of TBS with anthropometric parameters and 25(OH) vitamin D concentrations. Materials and Methods: The study group comprised 19 consecutive patients with CS (14 women and 5 men; mean age 45.84±13.15 years) and sex-, age-matched 36 controls (25 women and men; mean age 52.47±8.98 years). Anthropometric parameters, biochemical and hormonal data were compared between groups. Lumbar spine (L1-L4) and femoral neck BMD (LS BMD, FN BMD) measurements were performed. TBS values were obtained from lumbar spine DXA images. Results: TBS was significantly lower in patients with CS compared to controls (p=0.0002). The 10-year probability of hip fracture and the 10-year probability of a major osteoporotic fracture were significantly higher in the CS group than in controls (p=0.03, p<0.0001, respectively). All subjects from CS group with fractures had low TBS value (degraded microarchitecture). TBS correlated negatively with the duration of a disease in patients with CS (r=-0.590 p=0.008). Conclusions: The patients with active CS have altered bone microstructure as indicated by the decreased TBS and are at higher risk of fractures. TBS seems to be a very important analytical tool facilitating fracture risk assessment in endogenous hypercortisolism.